C Reactive Protein Concentrations can Predict Metabolic Syndrome in Adults (Medical Forum Monthly, 2024)
Objective: This study analysedthe correlations between C reactive protein (CRP) serum concentrations and demographics and anthropometric aspects of developing metabolic syndrome components in adults.Study Design: A cross-sectional study.Place and Duration of study: This study was carried out in Azad Kashmir Sheik Khalifa Bin Zyad Hospital Muzaffarabad from March 2012 to April 2013.Materials and Methods: Demographic, anthropometric parameters of MS such as body mass index (BMI) and waist hips ratio (WHR), biochemical and clinical data were collected from 115 adults of age ranged between 22-55yearsold.Results: Adults BMI had direct correlation with CRP concentrations. In our study CRP concentrations were statistical significant correlated with age (r = 0.282, p = <0.002),BMI (r = 0.787, p = <0.001), waist hips ratio (r = 0.850, p =< 0.001) and weight (r = 0.662, p =<0.001). The height had poor correlation with CRP (r = 0.101, p = 0.825).Thecorrected CRP (r = 0.101, p =0.825) was also poorly correlated to CRP concentrations.Conclusion: Statistical analysis has shown there is direct correlation between BMI, WHR and CRP concentrations which suggests that inflammation might be an important event in the development of metabolic disorders in adults.